2011
DOI: 10.1021/ja1039874
|View full text |Cite
|
Sign up to set email alerts
|

The Isomerization of Methoxy Radical: Intramolecular Hydrogen Atom Transfer Mediated through Acid Catalysis

Abstract: The catalytic ability of water, formic acid, and sulfuric acid to facilitate the isomerization of the CH(3)O radical to CH(2)OH has been studied. It is shown that the activation energies for isomerization are 30.2, 25.7, 4.2, and 2.3 kcal mol(-1), respectively, when the reaction is carried out in isolation and with water, formic acid, or sulfuric acid as a catalyst. The formation of a doubly hydrogen bonded transition state is central to lowering the activation energy and facilitating the intramolecular hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 24 publications
(33 reference statements)
4
91
0
1
Order By: Relevance
“…Intramolecular hydrogen abstraction, while thermodynamically favourable, is hindered by a significant barrier of the order of 19 kcal mol -1 . The (electronic) barrier for the 1,2-hydrogen shift is calculated to be even higher than this, which is in-line with very recent results on the 1,2-hydrogen shift of the methoxy radical 25 . The barriers for addition of the oxy-radical to the ortho-and ipso-positions of the β-phenyl ring are calculated to be significantly smaller, with values of around 10-11 kcal mol -1 for 1a.…”
Section: Resultssupporting
confidence: 90%
“…Intramolecular hydrogen abstraction, while thermodynamically favourable, is hindered by a significant barrier of the order of 19 kcal mol -1 . The (electronic) barrier for the 1,2-hydrogen shift is calculated to be even higher than this, which is in-line with very recent results on the 1,2-hydrogen shift of the methoxy radical 25 . The barriers for addition of the oxy-radical to the ortho-and ipso-positions of the β-phenyl ring are calculated to be significantly smaller, with values of around 10-11 kcal mol -1 for 1a.…”
Section: Resultssupporting
confidence: 90%
“…Although some recent reports [28][29][30][31][32][33][34][35][36][37] have demonstrated that water or acid can greatly reduce the activation barrier for various reactions, this is the first study on formic acid catalyzed hydration of SO 3 in the gas phase. Our results also confirm that this process is competitive with the reaction of SO 3 with the water dimer responsible for the formation of sulfuric acid and provide deeper insight into dissociation of the ground state of sulfuric acid, previously considered to be forbidden.…”
Section: Introductionmentioning
confidence: 93%
“…Insbesondere das schwefelzentrierte Radikal CH 3 OSO 2 kann leicht in SO 2 und das atmosphärisch bedeutende CH 3 O-Radikal zerfallen. [22] Abbildung 3. Berechnete Potentialenergie-Hyperfläche für die Isomerisierung von CH 3 SO 3 auf CCSD(T)/6-311 ++G(2df,2pd)-und CBS-QB3-Niveau( in Klammern).…”
Section: Methodsunclassified